2023
DOI: 10.1002/lary.30576
|View full text |Cite
|
Sign up to set email alerts
|

Office‐Based Treatment of Vocal Fold Polyps and Reinke's Edema: A Rational Comparison With Suspension Laryngoscopy

Abstract: ObjectiveBenign laryngeal lesions have traditionally been treated through suspension laryngoscopy under general anesthesia (GA). Recently, the development of operative videoendoscopes coupled with photoangiolytic lasers has allowed clinicians to treat these conditions in the outpatient clinic. We report our experience in the office‐based (OB) setting for the treatment of patients affected by vocal fold polyps (VFPs) and Reinke's edema (RE), comparing it to patients treated under GA.MethodsA retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Most recently, Filauro and colleagues evaluated 143 patients with BVFLs. 23 Notably, 88 patients had VF polyps treated by either OR microlaryngoscopy (37) or office-based photoangiolysis (51) using the 445-nm diode blue laser. The study evaluated VHI-10 and subjective evaluation of mucosal wave (rated as either "intact" or "impaired") at baseline and a single follow-up time of 2-4 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, Filauro and colleagues evaluated 143 patients with BVFLs. 23 Notably, 88 patients had VF polyps treated by either OR microlaryngoscopy (37) or office-based photoangiolysis (51) using the 445-nm diode blue laser. The study evaluated VHI-10 and subjective evaluation of mucosal wave (rated as either "intact" or "impaired") at baseline and a single follow-up time of 2-4 months.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in patient-reported outcomes measures are perhaps the most widely studied when evaluating responses to voice treatment. Significant improvement in Voice Handicap Index scores after treatment of BVFLs with both microlaryngoscopy 3,10,[22][23][24][25][26][27][28][29][30][31] and office-based laser treatment 22,23,[32][33][34] have been well documented. The primary outcome measure in this study is the VHI-10 score at 1 month after treatment.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this investigation agree with published reports on blue laser therapy for vocal fold lesions. Several papers have presented case series of patients treated with blue laser in-office such as Miller et al’s [ 18 ], Hamdan et al’s [ 19 ], Ghanem et al’s [ 20 ], Filauro et al’s [ 21 ] and Hamdan et al’s [ 22 , 23 ]. They have demonstrated the usefulness of this laser resecting laryngeal lesions in consultation in awake patients.…”
Section: Discussionmentioning
confidence: 99%
“…Campos et al [ 17 ] have reported the use of this blue laser on 38 patients under general anesthesia, using direct laryngoscopy techniques (Transoral Flexible Laser Surgery (TOFLS), showing it is a reliable tool to perform minimally invasive surgeries in the operating room using TOFLS techniques. Similarly, Miller et al [ 18 ], Hamdan et al [ 19 ], Ghanem et al [ 20 ], Filauro et al [ 21 ] and Hamdan et al [ 22 , 23 ] presented several case series of patients treated with in-office blue laser (TNFLS), concluding that this tool is effective for many laryngeal pathologies.…”
Section: Introductionmentioning
confidence: 99%